Storytelling as an Opening Communication Strategy: Exploring Speech Patterns in TEDx Talks - Deki Zulkarnaen; Adelowo Shamsudeen Opeyemi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
In contemporary public speaking, storytelling has become an influential communication strategy for attracting audience attention and enhancing message delivery. TEDx Talks, recognized globally for their engaging and inspirational presentations, frequently employ storytelling techniques in the opening sections of speeches to establish emotional connection and conceptual framing. This study explores how storytelling functions as an opening communication strategy in TEDx Talks. Using a qualitative content analysis approach, the research examines selected TEDx speeches to identify narrative structures, rhetorical patterns, and audience-oriented communication strategies embedded in speech openings. The findings reveal that storytelling in TEDx openings serves multiple functions, including building speaker credibility, stimulating emotional engagement, simplifying complex ideas, and creating audience curiosity. Furthermore, personal narratives and experiential anecdotes were found to be the most dominant storytelling forms used by speakers. This study contributes to communication studies by highlighting storytelling as a strategic rhetorical device in conventional or digital public speaking contexts and emphasizing its role in shaping audience engagement and persuasive communication